Aspergillus fuscicans (Aspergillaceae, Eurotiales), a new species in section Usti from Argentinean semi-arid soil - Romero, Stella Maris (2018)
Aspergillus fuscicans, a new species within Aspergillus section Usti from Argentinean semi-arid soil is introduced. Molecular, morphological and physiological studies were conducted, based on sequence analysis of partial β-tubulin and calmodulin sequence data. Aspergillus fuscicans formed a distinct, well-defined clade related to A. calidoustus and A. pseudodeflectus. In addition, A. fuscicans was able to grow and sporulate at 37 ºC, and had a negative Ehrlich reaction. Morphological and physiological features could be used to differentiate the new species from its phylogenetically related taxa.